Decentralizacja a efektywność sektora publicznego - Brol, Marcin (Decentralization of Efficiency in a Public Sector, 2008)
Decentralizing public finance and tasks is designed to increase the financial capacity of local governments. It should also enable to respond better to the needs of local communities. This paper attempts to analyze proposed changes on the basis of popular theoretical concepts: Pareto efficiency, Tiebout model, and aggregation of preferences. On their basis the author formulated postulates pertaining to the method and scope of the decentralization process. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 488-494